Turnover Intention Among Generation Z Employees: The Mediating Role of Burnout in the Relationship Between Workload - Subagyo, Tuntas; Nur Muftiyanto, Taufiq; Windarko, Windarko (Dinasti Publisher, 2024)
This study examines the phenomenon of turnover intention among Generation Z employees, focusing on the impact of workload with burnout as a mediating factor. Generation Z employees often perceive a high workload, leading to significant levels of burnout. This burnout subsequently contributes to their high turnover intention. The research employs a quantitative survey method, collecting data through questionnaires distributed to Gen Z employees across various industry sectors. The findings reveal a significant positive correlation between high workload and burnout levels. Additionally, burnout serves as a key mediator, exacerbating the turnover intention among Gen Z employees. The study further explores the role of human resource management strategies in managing workload and mitigating burnout. The implications of these findings suggest that organizations need to develop and implement effective human resource management strategies to reduce excessive workload and prevent burnout, thereby lowering turnover intention among Gen Z employees. By doing so, companies can retain valuable young talent and enhance overall organizational productivity.